The Future of Smart Tourism: Integrating AI, IoT, and Big Data for Enhanced Travel Experiences - Asep Koswara (Politeknik Pariwisata Palembang, 2025)
The rapid advancement of Artificial Intelligence (AI), the Internet of Things (IoT), and Big Data is transforming the tourism industry into a highly interconnected and intelligent ecosystem. This study, using a qualitative descriptive method, explores the contributions, benefits, challenges, and strategic implementation of these technologies in smart tourism. AI enhances personalization through chatbots, virtual assistants, and automated recommendations, while IoT enables seamless travel experiences through smart hotels and connected transportation. Big Data provides valuable insights for predictive analytics and demand forecasting, optimizing tourism management. Despite the advantages, challenges such as data privacy concerns, cybersecurity risks, and digital inequality remain significant barriers to adoption. Strategic implementation requires collaboration between governments, businesses, and technology providers, as well as investments in digital infrastructure and workforce training. By integrating these technologies effectively, the tourism industry can enhance visitor experiences, improve operational efficiency, and promote sustainable tourism development while ensuring an inclusive and secure smart tourism ecosystem.